TINJAUAN TERHADAP PELANGGARAN KODE ETIK JABATAN NOTARIS DI KABUPATEN PURBALINGGA - Yogi Priyambodo; Gunarto Gunarto (Jurnal Akta, 2017)
An insufficient Notary only owning membership of law but also have to base on responsibility and carrying out of to be august of ethics and prestige. Role and of Notary of vital importance to traffic punish in society, therefore Notary have to earn to run its profession professionally have, high dedication to and also always hold high standing and its prestige by upholding code of ethics Notary. So that can run its duty better as steward of society, a professional have to run its occupation by harmonizing among owned membership by respect code of ethics profession. Ethics is norms, rules and conditions, which must fulfill by a group of one who is conceived of by circle of professional. Therefore, of vital importance to all Notaries to be able to more comprehend of that deed can be told as collision of code of profession. Ethics, how organizational effectiveness Notary Indonesia in giving construction to all Notaries in order not to happen things which harming Notary and served society it.Pursuant to the things hence problems to check in this research: A Violations code of ethics, barriers and solutions Violations of code of conduct, as well as the legal consequences violations of the code of ethics by notary in district Purbalingga.Approach method the used is approach of empirical yuridis and specification of which is used in this research have the character of analytical descriptive research. Pursuant to result of research can be concluded supervisory council area district Purbalingga which acts as watching and collecting facts about the society and finding relations to violation and board of trustees having authority fall of sanctions to offenders, barriers experienced in the form of inadequate infrastructure, while the legal consequences about moral judgment and ethics Notary itself.Keywords : Violation, Code of Ethics